Targeting the HLC-1, LC-2/ad, and PC-14 lung cancer cell lines by the silver nanoparticles green-formulated by Descurainia sophia leaf extract - Jianjun Ge; Jianbo Wen; Mingjun Jiang; Kefeng Huang; Saichun Qi; Wei Huang; Linlin Tan (Molecular and Cellular Probes)
Descurainia sophia, as an an ethno-medicinal plant, contains antioxidant compounds that safeguard cellular integrity against various forms of damage and may play a role in cancer prevention. Antioxidant compounds present in this plant facilitate the body's production of new cells and diminish the risk of colon cancer. In recent years, silver nanoparticles synthesized through green methods using ethnomedicinal herbs have been employed in cancers treatment. We have conducted an investigation into silver nanoparticles that were synthesized through green chemistry principles, utilizing the Descurainia sophia leaves extract for lung carcinoma treatment. The efficacy of Ag NPs against prevalent lung cancer cells was assessed. The green-synthesized silver nanoparticles characterization was conducted utilizing X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), ultraviolet–visible spectroscopy (UV–Vis), energy-dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM). The findings from morphological analyses validate the nanoparticles spherical shape, which ranges in size from 20 to 60 nm. The IC50 values were determined to be 173, 125, and 109 μg/mL for HLC-1, LC-2/ad, and PC-14 cell lines, respectively. According to recent data, Ag NPs may be a useful option to support the treatment of lung cancer. Although the current study presents encouraging findings, further investigation is necessary to gain a deeper understanding of the mechanisms of action and potential side effects of silver nanoparticles on HUVEC cells.